Examining drug poisoning in child and adolescent psychiatric patients: clinical analysis and pharmacy services - Wang, Yuwen; Wu, Yuejing; Wang, Rongda; Wang, Zemin; Luo, Fugang (Frontiers in Psychiatry, 2025)
ObjectivesThis study aimed to investigate the clinical characteristics and symptoms of drug poisoning in adolescents with psychiatric conditions, and provide valuable guidance for pharmacists in the prevention and treatment of adolescent drug poisoning.MethodsA total of 84 adolescent patients with drug poisoning were recruited from January 2021 to December 2023. Clinical data of drug poisoning patients were analyzed, and pharmaceutical service implications were discussed based on hospital settings and patient medication profiles.ResultsFemale adolescents constituted a higher proportion of drug poisoning cases than males. Over 50% cases involved the overdose of two or more drugs, with quantities ranging from several pills to over a hundred. The drugs most commonly involved in overdose were psychiatric medications, including antidepressants (50.0%), antipsychotics (41.7%), sedatives/hypnotics (35.7%), and mood stabilizers (26.2%). Poisoning symptoms predominantly affected the nervous system, such as dizziness, headache, drowsiness, and unsteady gait, with most patients showing improvement after symptomatic treatment (94.0%).ConclusionOur study highlights the complex relationship between psychiatric disorders and intentional drug overdose among adolescents. Effective prevention strategies, including education on poison prevention, safe medication storage, and safety planning, are crucial for reducing intentional drug overdoses in this vulnerable population.